Experiences of using Aflibercept in diabetic macular edema treatment: data from routine clinical practice - E. Yu. Santoro (Российский офтальмологический журнал)
Purpose. To assess the effectiveness and safety of intravitreal aflibercept injections in clinically significant diabetic macular edema (DME) in a routine clinical practice.Material and methods. This was a prospective, observational, single-center study. During the study, anti-VEGF treatment naïve patients with clinically significant DME received five monthly intravitreal injections of aflibercept 2 mg followed by bimonthly injections. The observation period was 1 year.Results. The study included 11 eyes of 10 patients with clinically significant DME. Use of 8 intravitreal aflibercept injections resulted in central retinal thickness (CRT) reduction by 50 % from the baseline within 1 year of therapy. CRT decreased on average from 446.18 ± 106.88 μm to 226.27 ± 44.56 μm by the end of observational period. In addition, an increase in visual acuity was observed from an average from 0.33 ± 0.22 at the start of therapy to 0.62 ± 0.33 at the end of the observation. Serious adverse events over the entire period of treatment were not observed.Conclusion. Aflibercept showed high efficacy and safety in the treatment of clinically significant DME in routine clinical practice. To obtain optimal functional and morphological results in the treatment of patients with DME, it is necessary to start therapy with 5 loading intravitreal aflibercept injections.